2017
DOI: 10.1007/s00484-017-1357-6
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of surface type on the absorbed radiation by a human under hot, dry conditions

Abstract: Given the predominant use of heat-retaining materials in urban areas, numerous studies have addressed the urban heat island mitigation potential of various "cool" options, such as vegetation and high-albedo surfaces. The influence of altered radiational properties of such surfaces affects not only the air temperature within a microclimate, but more importantly the interactions of long-and shortwave radiation fluxes with the human body. Minimal studies have assessed how cool surfaces affect thermal comfort via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
(74 reference statements)
2
26
0
Order By: Relevance
“…The full detailed methods are found in Hardin and Vanos (2017) and Kenny (2008) [33,34]. Below, we outline any changes made from studies [21,28,32] for the given study.…”
Section: Thermal Environment Measurements Along the Marathon Coursementioning
confidence: 99%
“…The full detailed methods are found in Hardin and Vanos (2017) and Kenny (2008) [33,34]. Below, we outline any changes made from studies [21,28,32] for the given study.…”
Section: Thermal Environment Measurements Along the Marathon Coursementioning
confidence: 99%
“…However, higher solar reflectance within cities may also increase reflected solar radiation to near-surface facets and people [37,[51][52][53][54][55][56][57][58][59] although the magnitude of reflected solar radiation and its…”
Section: Urban Heat Mitigation-principles Of Reflective Technologymentioning
confidence: 99%
“…Additionally, via long-wave radiative transfer, hotter surfaces emit infrared radiation to cooler objects within view [51]. In summary, increasing surface reflectance-which in the solar spectrum is referred to as the surface's albedo-potentially reduces the surface's surface temperature, the convective transfer intensity to the air and the emitted infrared radiation to surfaces in view.However, higher solar reflectance within cities may also increase reflected solar radiation to near-surface facets and people [37,[51][52][53][54][55][56][57][58][59] although the magnitude of reflected solar radiation and its…”
mentioning
confidence: 99%
“…There have been significantly fewer surface temperature studies on other hard surfaces such as stone, ceramic and gravel [25][26][27][28], and on softer or pervious LEs such as mulch, sand, soils, turf grass or artificial turf grass, which are common features of domestic gardens [29][30][31][32]. Results for hard LEs, which demonstrated that smooth light-coloured materials were cooler whilst rougher, darker materials were warmer [27], were also applicable to soft LEs.…”
Section: Introductionmentioning
confidence: 99%